2021
DOI: 10.3390/cancers13205204
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Jak2 Inhibitors for Advanced Prostate Cancer: Are We Ready for Clinical Development?

Abstract: Androgen deprivation therapy (ADT) for metastatic and high-risk prostate cancer (PC) inhibits growth pathways driven by the androgen receptor (AR). Over time, ADT leads to the emergence of lethal castrate-resistant PC (CRPC), which is consistently caused by an acquired ability of tumors to re-activate AR. This has led to the development of second-generation anti-androgens that more effectively antagonize AR, such as enzalutamide (ENZ). However, the resistance of CRPC to ENZ develops rapidly. Studies utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 233 publications
(332 reference statements)
0
7
0
Order By: Relevance
“…We found that LR patients were more sensitive to chemotherapy with Tozasertib, a pan-Aurora inhibitor that exhibited enhanced carboplatin activity in platinum-sensitive and platinum-resistant ovarian cells of different p53 statuses. At low doses, the compound synergized paclitaxel-induced apoptosis and was active against paclitaxel-resistant cells ( 59 ). A phase I trial of 24-hour continuous intravenous volasertib in 27 patients determined that the disease was stabilized in almost half of the patients ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that LR patients were more sensitive to chemotherapy with Tozasertib, a pan-Aurora inhibitor that exhibited enhanced carboplatin activity in platinum-sensitive and platinum-resistant ovarian cells of different p53 statuses. At low doses, the compound synergized paclitaxel-induced apoptosis and was active against paclitaxel-resistant cells ( 59 ). A phase I trial of 24-hour continuous intravenous volasertib in 27 patients determined that the disease was stabilized in almost half of the patients ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, currently-available HDAC inhibitors have largely failed in clinical trials, mostly due to their toxicity [68] or lack of efficacy [69, 70]. Conversely, there are a number of ongoing clinical trials for JAK inhibitors – particularly JAK2 inhibitors – in advanced prostate cancer, but thus far these have not demonstrated sufficient monotherapy activity in men with mCRPC ([71]and see NCT00638378; closed due to lack of efficacy). Our data suggest that a number of critical and non-redundant pathways may be involved in enzalutamide resistance and lineage plasticity, suggesting the need for combination trial approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its role in IL-6 mediated signalling, the role of JAK has been explored as a potential therapeutic target to block PCa progression; however, this has proved a challenge. Ruxolitinib is a JAK1/2 inhibitor that reached Phase II trials for metastatic PCa, but the trial was terminated due to low efficiency (Trial identifier: NCT 00638378); however, this should be further investigated in the context of prolonged ADT with antiandrogens [48], where IL-6 signalling is more prevalent [49]. The Jak inhibitor AZD1480 initially also showed promise, suppressing metastasis in pre-clinical models [50]; however, three Phase I trials have been terminated due to unfavourable neurotoxicity profiles [48].…”
Section: Interleukin 6 Pathwaymentioning
confidence: 99%
“…Ruxolitinib is a JAK1/2 inhibitor that reached Phase II trials for metastatic PCa, but the trial was terminated due to low efficiency (Trial identifier: NCT 00638378); however, this should be further investigated in the context of prolonged ADT with antiandrogens [48], where IL-6 signalling is more prevalent [49]. The Jak inhibitor AZD1480 initially also showed promise, suppressing metastasis in pre-clinical models [50]; however, three Phase I trials have been terminated due to unfavourable neurotoxicity profiles [48]. Another stalling factor in JAK inhibitor development may be a lack of clinically representative cell-based assays [43].…”
Section: Interleukin 6 Pathwaymentioning
confidence: 99%